Performance analysis method for optical codes in coherent optical CDMA networks - Lee, S. W.; Green, D. H. (2000)
In the past, the selection of the address codes for coherent optical CDMA networks was carried out with the assumption that synchronisation at both sequence bit and data bit frame levels had been achieved throughout the networks at all times (totally synchronous (TS) systems). Establishing and maintaining global synchronisation requires costly and complex hardware. One way to alleviate this problem is to acquire synchronisation by coding only prior to the transmission of data bits (partially synchronous (PS) systems). It is shown that it is essential to consider the whole correlation output sequences of the correlation processes at the decoders in order to evaluate the correlation performance of address codes in the PS systems. A mathematical method is presented to simulate the correlation processes in such systems. The method is used to evaluate the PS system correlation performances of the address codes chosen previously for TS systems. It is shown that the address codes' performances in PS systems are generally worse than in TS systems, and that there is a need to design methods for selecting address codes with certain desired correlation performance levels in PS systems. The developed mathematical method will be useful for this purpose.